Evaluation of potential of fruit weight and fruit width and their interrelationships in the set of apricot genotypes - Vachon, Z. (International Journal of Horticultural Science, 2002)
Within the period of 1994-1999, variability of fruit weight and width was evaluated in altogether 24 apricot genotypes. It is concluded that the genotype and climatic conditions of individual years are the factors causing variability in these two parameters of apricot fruits. Variability of fruit weight was significantly higher (approximately 3-times) than that of fruit width. When evaluated on the base of their width, 75.0% and 95.8% of apricots were classified into the groups of extra and first quality, respectively. As genotypes with the maximum fruit width (i. e. above 50 mm) the following cultivars were classified: ’Velkopavlovicka LE-6/2’, ’NJA-1’, ’M 45’, ’M-25’ and lednicka (M-90-A)’. The value of fruit width (in mm) corresponded with its weight (in g) only within the range of 40 — 45 mm. With the increasing and/or decreasing size of apricot fruit the changes in fruit weight were more pronounced than in those in fruit width. Within the set of genotypes under study, this relationship may be expressed by the equation y = 0.1234 — 7.6605 + 152.76; the corresponding values of correlation coefficient and coefficient of curve determination are r = 0.95-H- and R2 = 0.959.